BATAS MINIMAL USIA PERKAWINAN DI INDONESIA DAN NEGARA MUSLIM - Pasaribu, Yunita; Hasanah, Uswatun (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2025)
This research aims to examine the minimum age for marriage in Indonesia and Muslim countries from a legal and socio-cultural perspective, and to conduct a comparative analysis. The method used is library research, with a normative juridical approach. The research findings indicate that the legal age for marriage in Muslim countries varies, influenced by legal, social, cultural, and political dynamics in each country. Indonesia has the highest minimum age for marriage, which is 19 years for both men and women. Meanwhile, in other countries like Pakistan and Egypt, the minimum age for marriage is lower, with some countries setting different ages for men and women. This difference is also influenced by the adopted school of thought, such as the Shafi'i school in Indonesia and Malaysia, the Hanafi school in Pakistan and Turkey, and the Maliki school in Morocco. Legal reforms in countries like Turkey and Morocco also reflect the adoption of secularization and gender equality principles. Pakistan stands out as the only country that imposes strict legal sanctions on those who violate the marriage age limit, while other countries like Indonesia rely on marriage dispensation regulations overseen by the courts.